The stage and the city : non-elite characters in the tragedies of Sophocles - Elodie, Paillard (Chorégie. Études, 2017)
The relationship between Classical Athenian tragedy and democracy remains a much-discussed problem which deserves to be examined from as many points of view as possible. Although Sophocles has sometimes been seen as less tied to his contemporary world than other authors, his works are nonetheless closely related to their democratic context, both as a product of their time and as a mean of encouraging their hearings to reflect on major political issues. This book explores the staging of non-elite characters in the seven extant tragedies of Sophocles and how they related to contemporary middling citizens. The structure of the fifth-century Athenian society underwent deep changes between the early and late plays of Sophocles. Appearance and growing political importance of a middling socio-political group of citizens played a crucial role in the development of Athenian democracy and this phenomenon is closely linked to the way in which non-elite characters are presented in Sophocles' plays. Lead to a better understanding of the links between Sophoclean tragedies and democracy, the book analyses the text of Sophocles' extant plays with you great care as it examined the structure of Athenian society on the basis of both historical and archaeological sources. The performance of Sophocles' tragedies not only reflected changes that took place in the structure of contemporary society but also fostered such changes by attributing increasingly active roles to characters with whom middling citizens could easily identify. -- publisher's website http://www.microsofttranslator.com/bv.aspx?from=fr&to=en&a=http%3A%2F%2Fwww.deboccard.com%2Ffr%2Fcategory%2F15028-Produit-9782701804309.html